2019
DOI: 10.1002/anie.201814566
|View full text |Cite
|
Sign up to set email alerts
|

One‐Step Synthesis of Dendritic Highly Branched Polystyrenes by Organotellurium‐Mediated Copolymerization of Styrene and a Dienyl Telluride Monomer

Abstract: Dendritic highly branched polystyrenes (HB-PSts) were prepared by ao ne-step copolymerization of dienyl telluride 6 and St in the presence of organotellurium chain transfer agent 2.T he molecular weight (MW), dendritic generation, and branching density were easily controlled by the ratio of 2 to 6 to styrene (St) with maintaining monodispersity.The branching efficiency estimated by adeuteriumlabeling experiment showed that 6 quantitatively (> 95 %) served as the branching point. The end group fidelity was high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…Furthermore, the method was extended to the synthesis of HB polystyrene (R 3 = Ph, R 4 = H) using 4aB (X = TeMe, R 1 = H, R 2 = C(CH3)=CH2) as a comonomer. 28 Our method uses radical polymerization, which is characterized by its high versatility in monomer species and can be extended to other important monomer classes, such as methacrylate derivatives (R 3 = CO2R, R 4 = CH3). However, extension of the use of 4aA and 4aB to methacrylates has been unsuccessful thus far (see below).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the method was extended to the synthesis of HB polystyrene (R 3 = Ph, R 4 = H) using 4aB (X = TeMe, R 1 = H, R 2 = C(CH3)=CH2) as a comonomer. 28 Our method uses radical polymerization, which is characterized by its high versatility in monomer species and can be extended to other important monomer classes, such as methacrylate derivatives (R 3 = CO2R, R 4 = CH3). However, extension of the use of 4aA and 4aB to methacrylates has been unsuccessful thus far (see below).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, new monomers, such as α‐bromo acrylates (Inibramer 1, Table 1) and α‐bromo styrenes, were used, where the initiating function of alkyl bromide was only enabled after the incorporation of monomer into polymer to convert the vinyl group to alkyl group so to effectively disable monomer‐monomer reactions in the polymerization (Li et al, 2019). Conditions have also been reported in the SCVP of AB 2 vinyl‐telluride monomers which follow the same pattern of initiator switching from inactive to active after vinyl radical addition (Inibramer 2, Table 1; Lu & Yamago, 2019).…”
Section: Branched Polymer Synthesismentioning
confidence: 57%
“…To alter this scenario, two special inimers, for example, vinyl tellurides and vinyl bromides, were separately designed, which could switch the reactivity of inimer initiating groups from dormant to active only after the reaction of vinyl group occurs. Vinyl tellurides were first reported in 2017 by Yamago group as the alkyl telluride initiating group was only turned on to be active after the vinyl group participated in the polymerization, achieving selective polymer–inimer reaction to produce hyperbranched structure with functionalizable alkyl telluride chain ends (Scheme 2, Figure 1c; Lu et al, 2017; Lu & Yamago, 2019). More recently, Zhong group designed a vinyl bromide inimer, termed inibramers to distinguish from traditional inimers, which exhibited a chain‐growth ATRP to produce hyperbranched polymers with alkyl bromide compositions.…”
Section: Branched Polymer Synthesismentioning
confidence: 99%
“…As precision synthesis has become a popular topic in polymer chemistry and materials, it is intriguing to find more research groups have showed interest to develop chain‐growth polymerization methods to achieve controlled synthesis of HBPs in one pot. These examples include i) the slow addition into dilute core method, ii) the use of a pair of B m core and AB n ( m , n ≥ 2) monomer with unequal reactivity of B group, iii) the use of monomers with to‐be‐activated initiating group to achieve polymerization‐induced branching …”
Section: Introductionmentioning
confidence: 99%
“…These examples include i) the slow addition into dilute core method, [17][18][19][20][21] ii) the use of a pair of B m core and AB n (m, n ≥ 2) monomer with unequal reactivity of B group, [22][23][24] iii) the use of monomers with to-be-activated initiating group to achieve polymerizationinduced branching. [25][26][27] In addition, efficient and quantitative installation of guest molecules onto selective domain of these HBP scaffolds was very difficult, which typically relies on chemical conjugation. Albeit dendritic polymers inherit abundant surface functional sites from their polymerization process, introduction of internal multi-functionality is synthetically complex and less reliable due to severe steric congestion.…”
mentioning
confidence: 99%